La littérature occitane dans les manuels scolaires - Marie-Jeanne Verny (Lengas)
This paper aims to analyse the place of Occitan literature in a corpus of textbooks published from the 19th century to the end of the 20th century. It points out the divergences and convergences, beyond time and space, in the choice of authors and the themes addressed. It also analyses the associated discourses: prefaces, pedagogical exercises, as to their scientific and ideological basis.